Market interest rate fluctuations : impact on the profitability of commercial banks. - Godspower-Akpomiemie, Euphemia Ifeoma (My University, 2013)
There are many functions of the financial system, with the basic function of transferring loanable funds from lender to borrowers (Rose et al, 1995). This financial transaction can be carried out directly or semi directly between lenders and borrowers. The shortcomings of direct and semi direct financing have opened doors for a third method—financial intermediation, which is done by financial intermediaries. Commercial bank is the classic example of financial intermediary at work. To achieve the goal of owners’ wealth maximization, banks should manage their assets, liabilities, and capital efficiently. In doing this, the bank should be conscious of the gap or spread between the interest income and the interest expenses paid, which is called net interest income (NII). Net interest income is a major part of banks’ profit, this is basically why the financial intermediaries try to offer lowest returns to savers and lend funds to borrowers at the highest possible interest rates. It is measured as net interest margin (NIM), which is NII divided by the average earning assets. This study examines the interest rate sensitivity of commercial banks’ interest profitability (Net Interest Margin) and net worth at the theoretical level and attempt to measure empirically the extent to which the interest profitability and net worth of commercial banks have been affected during the period of changing interest rates between 2001 and 2010. It as well measures the extent to which the factors that determine interest rate movement affect interest rate and which of the factors has more effect on interest rate. The measure of profitability captures the essence of lend-long borrow-short without directly including other determinants of bank income, such as loan loss and loan volume, which may be correlated with interest rates. It is also important to note that NIM is not a measure of total banks’ profits since it does not include non-interest income and expenses. A software package stata 10.0 was used to conduct the hypothesis testing, trend, and correlation analysis. The sampled banks are fourteen commercial banks and one investment bank in South Africa. The sampled banks were later divided into two groups (big and small), based on their assets size as at the year-end 2010. There are five (5) big banks with asset size of more than R100 billion and ten (10) small banks with asset size of less than R100 billion iii as at the year-end 2010. Analysis was further carried out separately on both the big and small banks to see the effect of interest rate fluctuations on them. Data required by the model was obtained from annual financial statements of the sampled banks for the period of ten years. It was found that fluctuations on interest rate (repo rate) affect the profit of commercial banks, but this effect is huge on small banks than the big banks. As the repo rate increases, the profit of commercial banks increases. Such effect of repo rate on profit of commercial banks was found to be statistically significant. It was also found that interest rate changes as well affect the net worth of commercial banks. The macroeconomic factors the determine the interest rates do not have direct effect on the banks’ profit, but have significant effect on the banks’ net worth, especially that of the small banks. As the rate of inflation, the rate of money supply, and uncertainty increase, the net worth of the small commercial banks in South Africa also increase. It could be advised that to maximize owners’ equity, South African commercial banks (big and small) should concentrate more on forecasting and controlling the determinants of the interest rates, rather than the interest rates themselves. It was also found that among the internal factors affecting profit and net worth of commercial banks, the liquidity ratio is most significant relative to capital ratio, competition, and non-performing loan.
Keywords: Interest rates; Banks; Profitability; South Africa